THE IMPACT OF LEADERSHIP STYLES IN THE DEVELOPMENT - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Leadership is the ability to employ managerial competencies to organized performance processes by inspiring, igniting and motivating teams to meet set organizational goals (Kirega, 2008).According to Ogbonnia (2007), an operational map for leadership was drawn along: corporate style, authoritative style, and laissez-faire style. At the organizational level, leadership establishes and transmits to all employees the overarching direction of the organization, as such, developing a better understanding of effective leaders is important for future leader development (Gupta, 2005). The European Foundation for Quality Management (EFQM), (2009) defines leadership at the strategic level as "how leaders develop and facilitate the achievement of the mission and vision, develop values required for long-term success and implement these via appropriate actions and behaviors, and are personally involved in ensuring that the organization’s management system is developed and implemented. To maintain a competitive edge, an organization must be able to adapt and change in order to improve processes. Leadership is a key component to achieving these outcomes (Keith, 2009).